Perancangan Sistem Informasi Berbasis Website Pada Toko Pualam Untuk Meningkatkan Efisiensi Layanan - Akmil Maulana Ramadhan; Kartini (Prosiding SISFOTEK, 2025)
This study aims to design and implement an e-commerce-based sales information system for Toko Pualam to enhance operational efficiency and expand marketing reach. The system was developed using the Prototype method, allowing iterative collaboration between developers and users to ensure that the final product meets real-world requirements. The research stages included requirement analysis, system design, implementation, and testing. The results indicate that the developed system supports online sales activities with key features such as product management, transactions, automated financial reporting, and real-time inventory control. Functional testing using Black Box Testing confirmed that all features operated as expected, while the System Usability Scale (SUS) test showed good usability levels. The implemented system effectively accelerates data processing and improves sales accuracy while providing customers with easy access to product information anytime and anywhere.